2019
DOI: 10.4274/haseki.galenos.2018.4514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Factors Affecting Survival in Patients with Gastric Cancer According to the 8th Edition of the Tumor, Node and Metastasis Classification

Abstract: We aimed to evaluate the effect of different parameters on survival in patients with gastric adenocarcinoma who underwent D2 lymph node dissection with more than 15 lymph nodes. Methods: A total of 161 patients with gastric adenocarcinoma, who underwent curative gastrectomy and had more than 15 lymph nodes dissected between January 2001 and January 2015, were retrospectively evaluated. A hundred and forty-six patients were included in the study. Results: The mean follow-up period was 24 (12-102) months and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…One of the important factors determining the overall survival of gastric cancer is the number of metastatic lymph nodes [23][24][25][26]. In this study, while NLR and GLR were significantly related to the number of metastatic lymph nodes, CAR was not.…”
Section: Discussionmentioning
confidence: 48%
“…One of the important factors determining the overall survival of gastric cancer is the number of metastatic lymph nodes [23][24][25][26]. In this study, while NLR and GLR were significantly related to the number of metastatic lymph nodes, CAR was not.…”
Section: Discussionmentioning
confidence: 48%
“…[ 12 , 14 , 16 ] There are also studies reporting that there is no relationship between perineural invasion and survival. [ 13 , 15 ] In this study, we found that the survival rate was lower in gastric cancer patients with perineural invasion as a result of univariate analysis.…”
Section: Discussionmentioning
confidence: 60%
“…[10] Survival rates have also been demonstrated to be lower in those with lymphovascular invasion in the previous studies. [11][12][13][14] However, Berkeşoğlu et al [15] reported that there was no relationship between lymphovascular invasion and survival. In our study, similarly, there was no difference between patients with and without lymphovascular invasion in terms of survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation